Individual Factors Affecting Learner’s Willingness to Speak in EFL Classroom - Syukri, Suhartini; Wahyuni, Sri; Abidin, Azwar (AL LUGHAWIYAAT, 2023)
This qualitative study aims at investigating what individual factors affecting learners Willingness to Communicate (WTC) in EFL classroom. Data were gernered using reflection which were distributed to 15 learners of the fifth semester at the English Education program in one of universities in Southeast Sulawesi. The researcher analyzed the learners’ reflection using thematic analysis (TA) through  coding  the  data  by underlining  code and conceptual framework  of WTC. The study result shows that several individual factors were identified as having an influence on learners’ willingness to speak, including perceived opportunity to communicate, emotions, interest, anxiety, feeling of insecurity, self-confidence, L2 proficiency and personalities. This study implies that these nine individual factors were found to be influential in effecting students’ WTC in English in this particular study, and the teachers need to pay more attention to these factors in providing instructions in EFL classroom.Keywords:    English foreign language classroom; English foreign language learners; individual factors; willingness to communicate.